9 Global longitudinal strain using feature tracking identifies the presence of chronic myocardial infarction in patients with normal LV ejection fraction. (18th April 2016) - Fent, G; Garg, P; Dobson, L; Musa, T Al; Foley, J; Greenwood, J; Plein, S; Swoboda, P
Abstract : Objectives: Chronic myocardial infarction (MI) detected by late gadolinium enhancement (LGE) is associated with significant mortality and morbidity. Limited subendocardial infarction may not lead to reduction in ejection fraction (EF) and a regional wall motion abnormality (RWMA) may not be evident. Global longitudinal strain (GLS) is impaired independently of EF in a number of conditions, enabling early detection of disease. Strain imaging predicts final infarct size in MI and is superior to LVEF in predicting morbidity and mortality. We hypothesised subjects with chronic MI but normal EF would have impaired GLS compared to healthy volunteers. Methods: Twenty patients with chronic MI (defined as subendocardial hyperenhancement on LGE) and normal LVEF and 20 healthy volunteers underwent CMR at either 1.5T or 3.0T (Philips Achieva TX). Standard bSSFP cine images were used to calculate LV dimensions and GLS by feature tracking (CVI 42, Circle Cardiovascular Imaging Calgary, Canada). LGE imaging was performed in all patients (0.2mmol/kg Gadolinium DTPA). Results: Patients were matched for age (59.8 ± 12 vs 59.6 ± 5.4 p = 0.95) and EF (60.4 ± 3.8 vs 62.2 ± 3.5 p = 0.11). Visual evidence of RWMA was present in 13/20 (65%) of chronic MI patients and 0/20 healthy volunteers. GLS was significantly lower in patients with chronic MI than in those without (−16.07 ± 3.9 vs −19.79 ± 2.3 p = 0.001) (Figure 1 ). Conclusion: GLS is impaired in patients with chronic MI but normal LVEF. GLS identifies abnormalities in LV systolic contraction not apparent with EF alone. It may reveal chronic MI in patients with contraindications to gadolinium-based contrast or prognostication of this subset of chronic MI patients. GLS could be used to detect chronic MI by alternative imaging modalities.